Eco-friendly and antibacterial finishes of organic fabrics using Herbal composite microencapsules - SUMATHI.S,; ANCY THOMAS, (International Journal of Pharma and Bio Sciences, 2017)
Due to great demand for antimicrobial textiles based on eco-friendly natural agents, herbal microcapsules were prepared using Curcuma aromatica, Camellia sinensis and Azadirachta indica at optimized conditions and finished onto bamboo and organic cotton fabrics. Optimization of microencapsulation process was carried out after determining the antibacterial activity of fabrics finished with three different concentrations of herbal capsules and three different shell materials by EN ISO 20645 and AATCC 100. Optimized microencapsulation was prepared using 3X herbal concentration and neem gum as shell materials. The optimized microcapsule finished fabrics showed increased bacterial reduction percentage (p<0.05). Maximum bacterial reduction percentage was observed for organic cotton fabrics against Escherichia coli (93%) and Staphylococcus aureus (96%). Topographical FESEM analysis of microcapsules finished fabrics revealed that the surfaces were very smooth and uniform. Microencapsulation method implied in this research was a unique method for imparting the pharmacological compounds of the herbal composite onto fabric materials permanently.